Humanized practices of obstetric nurses: contributions in maternal welfare - Alvares,Aline Spanevello (2018)
ABSTRACT Objective: To analyze the practice of obstetric nurses operating in a prenatal/delivery/postpartum unit of a university hospital in Mato Grosso and the maternal welfare resulted from the care provided in this scenario. Method: Study with a quantitative approach, carried out in a prenatal/delivery/postpartum unit of a university hospital in Cuiabá, Mato Grosso. The data were collected through the Scale of Maternal Welfare in Delivery Situation 2, and the study included 104 recent mothers in the period from June to September 2016. The data were analyzed in Epi Info version 7. Results: The results indicate that the practice of obstetric nurses is based on the humanization of labor and childbirth, however, the presence of invasive and unnecessary practices in the service did not influence the level of maternal welfare, which was optimum for 76% of the women. Conclusion: The lack of information might make the women less critical and, therefore, influence the evaluation of the care received